Constraints on cassava and yam research and production in Africa - Hahn, S. (1988)
The major tropical root crops cassava (Manilwt esculenta Crantz) and yams (Dioscorea spp.)-are widely grown and are mostly used as subsistence staples in many parts of the tropics and subtropics in Africa. They are the major source of energy for well over 200 million people on the continent. The leaves of cassava are often used as a vegetable providing protein, vitamins and minerals.